2012
DOI: 10.1001/jama.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Association Between <emph type="ital">BRCA1</emph> and <emph type="ital">BRCA2</emph> Mutations and Survival in Women With Invasive Epithelial Ovarian Cancer

Abstract: Context Approximately 10 percent of women with invasive epithelial ovarian cancer (EOC) carry deleterious germline mutations in BRCA1 or BRCA2. A recent report suggested that BRCA2 related EOC was associated with an improved prognosis, but the effect of BRCA1 remains unclear. Objective To characterize the survival of BRCA carriers with EOC compared to non-carriers and to determine whether BRCA1 and BRCA2 carriers show similar survival patterns. Design, Setting, and Participants We pooled data from 26 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
414
10
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 594 publications
(471 citation statements)
references
References 43 publications
31
414
10
16
Order By: Relevance
“…In addition to clinical and demographic factors, molecular biomarkers could be promising prognostic or predictive factors for EOC. For example, molecular epidemiological studies have demonstrated that the altered expression levels of BRCA1 and BRCA2 as a result of mutations are associated with individual variation of clinical outcomes of EOC patients 4, 5. The genomewide association study (GWAS) approach has also been used to identify susceptibility loci associated with clinical outcomes in European EOC patients 6.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to clinical and demographic factors, molecular biomarkers could be promising prognostic or predictive factors for EOC. For example, molecular epidemiological studies have demonstrated that the altered expression levels of BRCA1 and BRCA2 as a result of mutations are associated with individual variation of clinical outcomes of EOC patients 4, 5. The genomewide association study (GWAS) approach has also been used to identify susceptibility loci associated with clinical outcomes in European EOC patients 6.…”
Section: Introductionmentioning
confidence: 99%
“…30 Since that time, Soslow et al 23 validated the significance of different histologic patterns by describing variant morphologies (SET) in tumors with BRCA germline mutations that are associated with a better prognosis and a better response to chemotherapy. 3,4,[12][13][14][15][16][17][18][19] We previously reported on a separate cohort of high-grade serous carcinomas, showing an association between BRCA-positivity and variant histology (SET-like), younger age, a lower frequency of serous tubal intraepithelial carcinoma, and trends toward improved survival. 24 In this current study, we found that mutations in homologous recombination genes were 6 times more likely to be associated with nonclassic high-grade serous carcinoma histology (70%) than with classic high-grade serous carcinoma histology (28%) (P o0.001), and BRCA1 mutations were 10 times more likely to be associated with nonclassic high-grade serous carcinoma histology (P o 0.001) than classic histology.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The reliance on alternative end-joining repair pathways subsequently renders homologous recombination-deficient tumors more sensitive to chemotherapy as well as to PARPi. 3,4,[12][13][14][15][16][17][18][19] Only one PARPi has been FDA approved for the treatment of ovarian cancer, olaparib, and this is only in the setting of BRCA mutation and at least three prior lines of chemotherapy. Our findings further support the work of Pennington et al, 21 suggesting that a broader population of women with ovarian cancer may benefit from PARPi therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with BRCA mutation are at an increased risk of developing breast, ovarian, and other cancers [34]. More than 1 million women develop breast or ovarian cancer every year worldwide, and about 10% of them have a BRCA mutation [35][36][37], moreover that cancer patients with BRCA mutation have better outcomes than non-BRCA carriers [38,39]. And a recent study [40] suggested that BRCA mutation should be taken into account when devising therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%